Asparagus officinalis L. extract exhibits anti-proliferative and anti-invasive effects in endometrial cancer cells and a transgenic mouse model of endometrial cancer - Fang, Ziwei; Kong, Weimin; Zhao, Ziyi; Sun, Wenchuan; Xu, Guangxu; Clark, Leslie H.; Sullivan, Stephanie A.; Tran, Arthur-Quan; Zhou, Chang-Sheng; Sun, Delin; Zhao, Luyu; Wang, Jiandong; et al. (Frontiers in Pharmacology, 2024)
Introduction Endometrial cancer is the most common malignancy of the female reproductive system in the United States. Asparagus officinalis is a versatile, nutrient-dense, low-calorie vegetable that contains various bioactive metabolites that have shown a variety of biologic functions beneficial to health. The metabolites from asparagus officinalis extracts or asparagus officinalis extracts exhibit significant anti-tumorigenic activity in some pre-clinical models of cancer. Methods Endometrial cancer cells were used to study the effects of asparagus officinalis on anti-proliferation, anti-invasion and increased sensitivity to cisplatin, and obese and lean Lkb1fl/flp53fl/fl mouse model of endometrial cancer was used to study the role of asparagus officinalis in tumor growth. Results Treatment with increasing concentrations of Asparagus officinalis extracts significantly inhibited cell proliferation, reduced glycolytic activity, induced cellular stress and apoptosis, caused cell cycle G1 arrest, increased the sensitivity of cells to cisplatin, reduced cell adhesion and invasion, and activation of AMPK and inhibition of the AKT/mTOR and MAPK signaling pathways in endometrial cancer cells. Moreover, asparagus officinalis extracts suppressed cell adhesion and invasion through the modulation of the epithelial-to-mesenchymal transition process. Asparagus officinalis extract treatment for 4 weeks resulted in a significant reduction in tumor growth in Lkb1fl/flp53fl/fl mice under both obese and lean conditions, with a decrease in Ki-67 and vascular endothelial growth factor expression and an increase in Bip expression in endometrial tumors. Discussion These findings provide strong preclinical evidence for the potential therapeutic benefit of asparagus officinalis extract as a novel dietary strategy in the treatment of endometrial cancer. Further clinical trials of dietary intervention of asparagus officinalis or combination with cisplatin in patients with endometrial cancer are warranted.